The tech executive operating system : creating an R & D organization that moves the needle - Ben-Yosef, Aviv (Apress, 2021)
Leaders of tech organizations have to regularly adapt their strategies in an ever-changing market. Creating a culture that understands and supports both the technical and the nontechnical is a refined skill that can be difficult to master even for a leader with years of experience. The Tech Executive Operating System helps you apply your personal expertise and build a thriving R & D organization that moves the needle. Tech companies spend an average of 15% of their revenue on R & D. As they grow, they find the return on this large investment decreases at a fast pace. Executives and leaders of companies big and small are at a loss and seeking guidance. Author Ben-Yosef expertly walks you through the need to set goals, translate business objectives to R & D terms, and establish the organizational structures and processes to create the biggest impact. The Tech Executive Operating System is a rare book that provides useful yardsticks to measure the progress and contributions of managers, teams, and individuals in your organization. Tech executives, first-time startup founders, managers, CEOs, and other non-technical founders of startups who want to better understand a significant part of their organization all have invaluable knowledge to gain from The Tech Executive Operating System. Ben-Yosef's thorough research and real-world examples enhance the lessons and make your goals clear. Engineering organizations can be vastly improved by this multi-faceted approach, and the future of tech is calling for it.